PRAKTIK SHARED VALUE PADA INDUSTRI KECIL BATIK SUMENEP MADURA - Oki Rahadianto Sutopo (Jurnal Universitas Paramadina, 2014)
AbstractThe configuration of cooperation between industry, government and society  has experienced a shift from partial process to integrative process, from top down to bottom up. One of the triggers of these changes is the practice of cooperation based on shared value. A cooperation based on the production of competitive shared value’s orientation, based on its potential and social economic condition. It is hoped that shared value will create a  new changes. The actors are not only from the big city, but also we can  find the practice of shared value among small-scale batik industry in  Sumenep region, Madura. In this article, the empirical data about shared  value among actors of small-scale batik industry that have strong religious  background was obtained through in-depth interview and  observation. The embededness of value creates a bondedness of trust  among the actors who cooperate in the small-scale batik industry.